Resistance of rose rootstocks to Meloidogyne hapla nematode - Pizetta, P. U C [UNESP]; Pivetta, K. F L [UNESP]; Santos, J. M. [UNESP]; Batista, G. S. [UNESP]; Gimenes, R. [UNESP]; Martins, T. A. [UNESP] (My University, 2010)
Roses are widely used in landscaping. One of the most important fitossanitary problems of this ornamental plant in gardens is the fitonematodes, especially Meloidogyne hapla, which is the most important one in colder climate regions. This work had the objective of study the resistance of nine rose rootstocks (Rosa multiflora 'Paulista', R. multiflora 'Japanese', R. multiflora 'Iowa', R. multiflora 'Kopman's', R. indica × multiflora, R. indica 'Mayor', R. sp. 'Natual Brier', R. manetti and R. canina 'Inermis') to Meloidogyne hapla nematode. Ten replications of each rootstock were used. The roots, collected in a commercial area of cut roses, visually had galls there were isolated and identified. The inoculum of M. hapla was previously produced in rose and tomatoes seedlings under greenhouse conditions. The plants were harvested ninety days after inoculation. The roots were washed and the number of eggs and juveniles recuperated in the root system of each plant was estimated by the Final Population (FP), and the Reproductive Factor (RF) was calculated. The rootstocks with RF<1 values were considered resistant, and the ones with RF>1, susceptible. Rosa manetti and Rosa sp. 'Natual Brier' rootstocks showed the lowest values for RF, indicating that, although they are susceptible, they provide the lowest nematode reproduction. Based on the RF values, it was concluded that all the rose rootstocks evaluated were susceptible to M. hapla nematode.
Keywords: Fitonematodes; Reproductive factor; Rosa spp; Seedling; Susceptibility; Lycopersicon esculentum; Meloidogyne hapla; Rosa; Rosa canina; Rosa indica; Rosa multiflora; Rosa sp.